Ocorrência de Ungla Navás (Neuroptera, Chrysopidae) no Brasil e descrição de nova espécie - Freitas, Sérgio de [UNESP] (Sociedade Brasileira de Entomologia, 2007)
Pela primeira vez é registrada a ocorrência do gênero Neotropical Ungla Navás, 1914 em ecossistema brasileiro. Uma nova espécie é descrita para Sete Lagoas, Minas gerais, Brasil. Uma chave para espécies de Ungla é fornecida.

The Neotropical genus Ungla Navás, 1914 is recorded for the first time in the Brazilian ecosystem. A new species is described from Sete Lagoas, Minas Gerais, Brazil. A key for the Ungla species is added.
Occurrence of Ungla Navas (Neuroptera, Chrysopidae) in Brazil and description of a new species
Keywords: Bicho lixeiro; controle biológico; predador; Biological control; green lacewings; predator